Чинники трансформації бізнес-процесів в розвитку індустрії 4.0 - Балаклеєць, К. Ю.; Родченко, В. Б.; Balakleiets, K.; Rodchenko, V. (Видавництво Львівської політехніки, 2024)
Узагальнено підходи до оцінки проблематики цифрових трансформацій бізнес- процесів у системі Індустрії 4.0 з акцентом на поведінкові складові. Виявлено ключові факторів, що впливають на ефективність впровадження новітніх технологій та їх взає- модію з корпоративною культурою. Використовуючи системний аналіз, досліджується вплив поведінкових аспектів на успішність цифрової трансформації та розробку стратегій інтеграції технологій Індустрії 4.0 у бізнес-процеси. Висновки підтверджують необхідність адаптації корпоративної культури та розробки стратегій, що враховують людський фактор для успішної реалізації цифрових трансформацій.

Purpose – This study delves into the intricate challenges of digital transformation in business processes within the Industry 4.0 framework, emphasizing the significance of behavioural factors. The primary objective is to identify and dissect the critical determinants that influence the successful integration and utilization of advanced technologies. Moreover, the research explores how these technologies interact with corporate culture to drive improvements in business efficiency, productivity, and overall competitiveness in today's fast-evolving digital landscape. Design/methodology/approach – The research employs a thorough and systematic methodological framework, integrating a broad literature review with qualitative and quantitative analyses. It explores the connections between digital transformation, corporate culture, and the strategic role of marketing in operational management. The study evaluates both immediate and long-term effects of Industry 4.0 technologies on business operations, focusing on their potential to foster innovation and enhance operational excellence. Furthermore, the research critically examines the role of corporate culture in the successful integration of new technologies, providing insights into the necessary cultural adaptations that enable organizations to fully leverage the benefits of Industry 4.0. Findings – The findings highlight the essential role of a flexible and adaptive corporate culture in the effective integration of Industry 4.0 technologies into organizational processes. The research shows that companies with a strong alignment between their cultural values and technological strategies are more likely to achieve significant gains in operational efficiency and market adaptability. The study also emphasizes the critical need for strategic alignment between marketing and operational management, demonstrating that this integration is crucial for maintaining a competitive edge in an increasingly unpredictable market landscape. Additionally, the study identifies specific challenges inherent to the digital transformation process, such as resistance to change and the continuous need for skill development, and offers strategic solutions to overcome these barriers. Practical implications – The research provides valuable insights for companies aiming to enhance their operational performance and competitive positioning through the adoption of advanced technologies. The study offers a comprehensive framework for understanding how Industry 4.0 can be strategically utilized to improve customer engagement and optimize internal processes, ensuring sustainable competitiveness in the long term. Originality/value – This study adds to the existing literature by offering an in-depth analysis of the interplay between marketing and operational management in the context of Industry 4.0. The research highlights the importance of aligning corporate culture with technological progress to achieve long-term business success. The conclusions underscore the necessity for companies to embrace digital transformation as a holistic process that involves strategic, operational, and cultural shifts.
Factors of business process transformation in the development of Industry 4.0
Keywords: Індустрія 4.0; цифрова трансформація; бізнес-процеси; мар- кетинг; операційний менеджмент; корпоративна культура; Industry 4.0; digital transformation; business processes; marketing; operational management; corporate culture; M19; O33; 658.5; 004.89; 658.8